Efektifitas Program Anakku Sehat dan Cerdas Terhadap Keragaman Makanan dan Status Gizi anak PAUD - Heni Hendriyani; Susi Tursilowati; Istiwa Ahlul Kafi (Poltekkes Kemenkes Semarang, 2023)
Background: Indonesia still facing child nutrition problems even though the government has made maximum efforts, but the prevalence of stunting in children under five years (toddlers) remains high at 30.8% in 2018. Based on 2018 Riskesdas data, the prevalence of children aged 0-23 months who were stunting in districts Brebes is much higher than the prevalence of Central Java Province, namely 27.31% and 13.87%, respectively. Objectives: to determine the effect of the My Healthy and Smart Child Program intervention on food diversity and the nutritional status of PAUD children in Kluwut village. Methods: Quasi-experimental research design with one group post test only. Respondents were mothers of PAUD children and the sample were PAUD children selected by purposive sampling. Data collected on respondent characteristics such as gender, child's age, mother's age, father's age, mother's education, father's education, family income, and number of families, food diversity, food intake, and children's nutritional status. Data was collected by questionnaire, food recall form, FFQ form, and anthropometry. The number of samples were 65. Data analysis included univariate and bivariate analysis (dependent t test). Result: The data shows that there is no diversity difference on nutrition intake diet and the nutritional status before and after the intervention. However, there was a difference in the respondents' fat intake after the intervention (p0.05). Conclusion: The intervention period was relatively short therefore the effect of the intervention had not manifested on intake and nutritional status. In addition, the intervention material provided should focus more on improving nutritional intake